Psychological Assessment with Objective and Projective Techniques along with Self-Report: A Case Study of Young Widow with Major Depressive Disorder - Saima Khan, Maria Rafique, Sobia Ikram, (Pakistan Journal of Medical & Health Sciences, 2022)
The study investigated the psychological concerns of a young widow, who lost her husband just at the age of 21 and examined how psychotherapeutic techniques helped her overcome them in the present case study. Using a structured clinical interview and a complete report, we documented the impact of this significant loss on both temperament and emotional wellbeing. Including the Beck Depression Inventory (BDI), The Standard Progressive Matrices (SPM), Thematic Apperception Test (TAT), Rotter’s Incomplete Sentence Blank (RISB), Bender Gestalt Test (BGT), and Human Figure Drawing Test (HFD). These studies were crucial in assessing a diagnosis as well as a treatment strategy. The girl had a significant depressive episode and met all the diagnostic criteria. In similar circumstances, this mixture of psychological testing could help establish an accurate diagnosis and comprehend the behavioral and psychological consequences of Major Depressive Disorder (MDD). The study also indicated that Cognitive Behavior Therapy (CBT) is an effective treatment option for people suffering from Major Depressive Disorder.